Static, dynamic and creep behaviour of a full-scale GFRP-SFRSCC hybrid footbridge - Gonilha, José (2014)
A three-year research project (Pontalumis) was carried out for the development of an innovative simply supported hybrid footbridge, with 11 m of length and 2 m of width. The footbridge is composed of two pultruded I-shaped glass fibre reinforced polymer (GFRP) girders (400×200(×15) mm2) bonded and bolted to a 37.5 mm thick deck in steel fibre reinforced self-compacting concrete (SFRSCC). The present paper describes the material/structural concept of this footbridge, its design and construction process, and summarizes the response of the prototype when submitted to static short and long-term load tests, and dynamic load tests. The prototype was simple and fast to execute, presenting a reduced dead-weight of only about 3 tonf. The static and dynamic behaviour of the prototype as well as its long-term deflection fulfil standards’ requirements for footbridge structures and are in good agreement with conventional analytical and numerical design tools.